Topical sustained drug delivery to the retina with a drug-eluting contact lens. (October 2019) - Ross, Amy E.; Bengani, Lokendrakumar C.; Tulsan, Rehka; Maidana, Daniel E.; Salvador-Culla, Borja; Kobashi, Hidenaga; Kolovou, Paraskevi E.; Zhai, Hualei; Taghizadeh, Koli; Kuang, Liangju; Mehta, Manisha; Vavvas, Demetrios G.; et al.
Abstract: Intravitreal injections and implants are used to deliver drugs to the retina because therapeutic levels of these medications cannot be provided by topical administration (i.e. eye drops). In order to reach the retina, a topically applied drug encounters tear dilution, reflex blinking, and rapid fluid drainage that collectively reduce the drug's residence time on the ocular surface. Residing under the tears, the cornea is the primary gateway into the eye for many topical ophthalmic drugs. We hypothesized that a drug-eluting contact lens that rests on the cornea would therefore be well-suited for delivering drugs to the eye including the retina. We developed a contact lens based dexamethasone delivery system (Dex-DS) that achieved sustained drug delivery to the retina at therapeutic levels. Dex-DS consists of a dexamethasone-polymer film encapsulated inside a contact lens. Rabbits wearing Dex-DS achieved retinal drug concentrations that were 200 times greater than those from intensive (hourly) dexamethasone drops. Conversely, Dex-DS demonstrated lower systemic (blood serum) dexamethasone concentrations. In an efficacy study in rabbits, Dex-DS successfully inhibited retinal vascular leakage induced by intravitreal injection of vascular endothelial growth factor (VEGF). Dex-DS was found to be safe in a four-week repeated dose biocompatibility study in healthy rabbits. Graphical abstract: Image 1 Highlights: Contact lens Dexamethasone Delivery System (Dex-DS) released dexamethasone for 7 days in vitro and in vivo in rabbits Dex-DS topically delivered therapeutic amount of dexamethasone to back of the eye Dex-DS inhibited VEGF-induced retinal vascular leakage in rabbits Dex-DS was demonstrated to be safe in a 4 week repeated use biocompatibility study Des-DS offers a therapeutic alternative to intraocular injections